Incorporating learning how to learn in a Malaysian Lower secondary smart classroom - Lau, Bee Yian (2004)
This study w3s shaped by hvo major phases of investigation. In the first phase, a control and experimental group was used. The experimental group was only exposed to lessons which were based en Learning How To Learn. The); mere not trained in learning strategies. SILL was administered to this experimental group at the beginning and end of Phase One. The findings revealed that there is a slight improvement in the mean scores of all the strategies at the end of Phase One except for meta cognitive strategies. A pilot study had revealed that many teachers teaching Form One English Language Smart Classes did not know how to implement learning strategies and learning styles into their English lessons. Hence, in the second phase of the study, both teachers and students following the English Language classes in the Form One Smart classes were given training in Learning How To Learn. A Training Module for Teachers was designed to make Form One teachers in the English Language Smart classroom aware of the key concepts of Learning How To Learn which included learning strategies, learning styles, learning contracts and learner autonomy. Knowledge of learning styles and being able to identify the types of learners in a class would help teachers plan their lessons better. Teachers were also trained to write Learning How To Learn lesson plans as well as to know the criteria for material selection. The findings showed that this trainin2 sensitize the teachers to teach using Learning How To Learn. On the other hand, the Training Module for Learners is, in particular, awareness training in Oxford's six classes of learning strategies. Learners also discovered their own learning styles when they were answered the questionnaire on Willing's Learning Styles Tasksheets. The findings indicated that with training, students could become better language learners as they h a ~ ea knowledge of their own learning styles and preferred learning strategies. Students could also be given autonomy to decide on what is to be learnt, why it is to be learnt, when and where it is to be learnt and how it is to be learnt. The Training Module for Teachers was evaluated by the English Panel of Sekolah Menengah Sains Kuching whereas the Training Module for Learners was evaluated by four educators and the learners themselves. On the whole, the findings revealed that the two modules were workable and in line with the principles of Learning How To Learn.